Do trophic subsidies affect the outcome of introductions of a non‐native freshwater fish?. (11th July 2013) - Jackson, Michelle C.; Allen, Rachel; Pegg, Josephine; Britton, J. Robert
Summary: Understanding how environmental variables and human disturbances influence the outcomes of introductions of non‐native freshwater fish is integral to their risk management. This can be complex in freshwater ecosystems that receive subsidies that increase food availability, as these may influence the outcome of introductions through promoting the survival, reproduction and establishment of the introduced propagules through increasing their access to food resources. We determined how natural and/or artificial trophic subsidies affected the reproduction and establishment of the introduced topmouth gudgeon ( Pseudorasbora parva ) in replicated pond mesocosms. The mesocosms all started with eight mature fish and were run for 100 days during their reproductive season. The subsidies consisted of natural terrestrial prey and/or fishmeal pellets (a common trophic subsidy that can be significant in systems that are used as sport fisheries or for aquaculture). After 100 days, fish in the natural subsidy ponds showed minimal growth and very low reproductive output. Analysis of δ 13 C and δ 15 N indicated that their progeny, 0+ fish produced in the ponds, exploited the terrestrial prey. By contrast, in ponds where pellets were added, mineral nutrient availability and primary production were significantly increased, and the mature fish fed mainly on the aquatic resources. The increased productivity of the ponds significantly increased fish growth and fitness, resulting in high numbers of 0+ individuals that did feed on the pellets. Thus, subsidies that can increase both primary production and food resources (such as pelletised fishmeal) can significantly influence the ability of colonists to establish a population rapidly. Management efforts to minimise the risk of introductions should thus consider the role of these types of allochthonous subsidies.